On Frenet Framme of Null Curves in Three Dimensional Minkowski Spaces - Anis Saad; Awatif Mousay (AlQalam Journal of Medical and Applied Sciences, 2025)
This article investigates the Frenet frame of null curves which are embedded inside three-dimensional Minkowski spacetime M^2,1, a significant topic of differential geometry and Lorentzian geometry. Unlike Euclidean geometry, the indefinite metric of Minkowski space introduces unique challenges and properties. We analyse the Frenet frame components, including the tangent of curves, and normal which is orthogonal, and binormal this is a perpendicular to both vectors, and derive the associated Frenet-Serret equations. Additionally, we propose new formulations for these equations specific to null curves in the Minkowski space. A practical example is visualized using Maple to illustrate the theoretical results. This study contributes to the deeper understanding of the geometric behaviour of null curves in Lorentzian settings. تتناول هذه الورقة دراسة الإطار الفرياني للمنحنيات العدمية في فضاء مينكوفسكي ثلاثي الأبعاد يتم التركيز على خصائص الإطار الفرياني لهذه المنحنيات، والذي يشمل الاتجاهات الثلاثة: المماس، العادي، والمماس الثنائي، بالإضافة إلى المعادلات التفاضلية المرتبطة بها. يُعد هذا الموضوع مهمًا في الهندسة التفاضلية، خاصة في دراسة هندسة لورنتزية، حيث تضيف الطبيعة غير المحددة لمتري مينكوفسكي تعقيدًا إضافيًا مقارنة بالهندسة الإقليدية. تتضمن الدراسة استنتاج صيغ جديدة لمعادلات الإطار الفرياني في حالة المنحنيات العدمية. كما يتم تقديم مثال عملي معروض باستخدام برنامج "Maple" لتوضيح النتائج. المنحنيات العدمية في فضاء مينكوفسكي تظهر اختلافات جوهرية في السلوك والخصائص مقارنة بالفضاء الإقليدي. حيث ان تطبيق تحويلات لورنتز يؤدي إلى تغييرات في خصائص المنحنى، مما يدل على عدم الاستمرارية في هذه الحالات. الورقة تقدم رؤية جديدة لدراسة المنحنيات العدمية، مع الإشارة إلى العمل المستقبلي لتوسيع هذه الدراسة إلى أطر موازية في فضاء مينكوفسكي